Indirect procurement management: Maturity model development and validation - Liinaharja, Kalle (My University, 2023)
Indirect procurement management still lags direct procurement in many aspects. Whereas the value creation capability and strategic contribution of direct procurement are widely recognized, indirect procurement is often seen as overly complex, minor, and irrelevant compared to direct procurement. As a result, it receives much less managerial attention and resources, degrading the efforts to manage them professionally. Yet, indirect procurement often represents more than 40 percent of all procurement spend – a share that no company should overlook. With ever toughening competition, indirect procurement management development has the potential to offer a new source of savings and competitive advantage. However, there is only little academical support for developing indirect procurement management. The literature of indirect procurement is also very fragmented, and a large part of it dates to 1990s and 2000s. This study aims to create a synthesis of indirect procurement research and bridge the gap between academia and practice by creating a comprehensive research-based tool for measuring and developing indirect procurement management capability. Maturity models have been recognized as useful tools to measure current capability and guide development. Therefore, this study creates an indirect procurement management maturity model. This thesis adopts a constructive approach to developing the maturity model. The first version of the model is created through an extensive literature review and is then empirically validated by conducting qualitative research utilizing semi-structured interviews. Two research questions are first posed to guide the process and later answered: Which issues and management practices characterize indirect procurement management? and What are the characteristics of a comprehensive indirect procurement maturity model? The study identified multiple issues and managerial solutions characteristic for indirect procurement management that are present at different stages of maturity. The issues are intertwined in their root causes and require comprehensive development and implementation of best practices to be overcome. The developed maturity model was seen to accurately reflect reality and to be a useful tool to measure current capability and to guide indirect procurement management development in practice. Improvements with soft factors, such as communication, cross-functional cooperation, and managerial recognition, were recognized as key enablers and solutions for improving indirect procurement management performance. When properly resourced, correctly appreciated, and comprehensively developed indirect procurement can offer a sought-after source of untapped potential in cost reduction and value-creation and improve everything from functional performance to work-wellbeing of all employees in an organization.

Epäsuorat hankinnat ovat jääneet suorien hankintojen varjoon niin yrityselämässä kuin tutkimuksessakin. Suorien hankintojen arvonluontipotentiaali ja strateginen merkitys ymmärretään käytännön yrityselämässä, mutta epäsuorat hankinnat nähdään edelleen usein kompleksisena ja merkityksettömänä osana hankintoja. Epäsuoriin hankintoihin ei kiinnitetä tarpeeksi huomiota eikä niille allokoida riittävästi resursseja, joka heikentää merkittävästi niiden johtamista ja kyvykkyyttä. Epäsuorat hankinnat vastaavat kuitenkin usein yli 40 prosentista hankintakuluja. Ne ovatkin siis merkittävä kokonaisuus, jota yhdenkään yrityksen ei tulisi väheksyä. Epäsuorien hankintojen kehittämisessä piilee suurta potentiaalia kulusäästöille ja kilpailukyvyn kehitykselle. Akateeminen kirjallisuus tarjoaa kuitenkin vain vähän tukea niiden kehittämiselle. Epäsuorien hankintojen johtamisen kirjallisuus on hyvin hajanaista ja merkittävä osa siitä yli 20 vuotta vanhaa. Tämän tutkielman tavoitteena on luoda synteesi epäsuorien hankintojen kirjallisuudesta ja kuroa umpeen akateemisen maailman ja käytännön välistä kuilua luomalla kattava ja ajantasainen, tutkimukseen perustuva työkalu epäsuorien hankintojen johtamisen kyvykkyyden mittaamista ja kehittämistä varten. Maturiteettimallit on tunnistettu hyviksi työkaluiksi kyvykkyyden mittaamiseen ja kehitystoimien ohjaamiseen. Tässä tutkimuksessa luodaankin maturiteettimalli epäsuorien hankintojen johtamiselle ja validoidaan se empiirisesti. Maturiteettimalli kehitetään konstruktiivista tutkimusotetta soveltaen. Mallin ensimmäinen versio luodaan kattavan kirjallisuuskatsauksen pohjalta, jonka jälkeen se validoidaan laadullisen tutkimuksen avulla puolistrukturoituja haastatteluja aineistonkeruussa hyödyntäen. Tutkimuksen tueksi asetetaan kaksi tutkimuskysymystä, joihin vastataan lopuksi. Nämä kysymykset ovat: Mitkä ongelmat ja hankintojen johtamisen käytännöt ovat tyypillisiä epäsuorille hankinnoille? Sekä Mitkä ovat kattavan epäsuorien hankintojen maturiteettimallin tunnuspiirteet? Tutkielmassa identifioitiin monia epäsuorien hankintojen johtamiselle tyypillisiä ongelmia ja ratkaisuja, jotka esiintyvät eri tavalla maturiteettipolun eri vaiheissa. Ongelmien juurisyyt liittyvät toisiinsa ja ratkaisujen implementointi edellyttää kokonaisvaltaista kehitystä. Kehitetyn maturiteettimallin nähtiin olevan realistinen ja hyödyllinen työkalu nykyisen kyvykkyyden mittaamiseen ja kehittämiseen. Viestinnän, poikkifunktionaalisen yhteistyön ja johdon huomion ja ymmärryksen lisääminen epäsuoria hankintoja kohtaan tunnistettiin olevan avainasemassa epäsuorien hankintojen johtamisen kehittämisessä. Asianmukaisen resurssoinnin, oikeanlaisen arvostuksen, sekä kattavan kehittämisen kautta epäsuorat hankinnat voivat tarjota arvokkaan kilpailukyvyn lähteen, sekä parantaa organisaatioiden sisäistä kyvykkyyttä jokaisella osaalueella.
Keywords: Indirect procurement, Indirect procurement management, Procurement, Maturity model, Maturity measurement, Epäsuora hankinta, Epäsuorien hankintojen johtaminen, Hankinta, Maturiteettimalli, Maturiteettimittaus